PARENTAL PARTICIPATION TO MOTIVATE STUDENTS IN LEARNING ENGLISH DURING COVID-19 PANDEMIC: THE CASE OF INDONESIAN SECONDARY SCHOOL STUDENTS - Kheryadi; Fitri Hilmiyati; Husnul Hotimah (Getsempena English Education Journal, 2021)
This research seeks to investigate the role of parents in the success of children's education. It is intended to evaluate parents' role and evaluate the participation of parents in the success of elementary school students in learning English. The qualitative approach was used in this study to derive the findings by using a questionnaire and documentation from the research subject. In this report, there are 28 students and parents involved. Furthermore, the data processing method is used to accumulate the data, reduce the data, show the data, and make a conclusion. The outcome of this research is a perfect reflection of the standards of English learning success by parents. In learning vocabulary, parents understand the limitations and challenges of their children. Parents' role is also excellent; 91 percent of parents help children learn English provides benefits, and positively affect children. Then, 23 percent of parents are only interested in getting support at home with children's education; therefore, the family or siblings can help unless the child has problems.